Hydrogen sulfide: a new endogenous player in an old mechanism of plant tolerance to high salinity - da-Silva, Cristiane J.; Modolo, Luzia V. (Acta Botânica Brasílica, 2018)
ABSTRACT High salinity affects plants due to stimulation of osmotic stress. Cell signaling triggered by nitric oxide (NO) and hydrogen sulfide (H2S) activates a cascade of biochemical events that culminate in plant tolerance to abiotic and biotic stresses. For instance, the NO/H2S-stimulated biochemical events that occur in plants during response to high salinity include the control of reactive oxygen species, activation of antioxidant system, accumulation of osmoprotectants in cytosol, induction of K+ uptake and Na+ cell extrusion or its vacuolar compartmentation among others. This review is a compilation of what we have learned in the last 10 years about NO participation during cell signaling in response to high salinity as well as the role of H2S, a new player in the mechanism of plant tolerance to salt stress. The main sources of NO and H2S in plant cells is also discussed together with the evidence of interplay between both signaling molecules during response to stress.